Amorphization of Ethenzamide and Ethenzamide Cocrystals-A Case Study of Single and Binary Systems Forming Low-Melting Eutectic Phases Loaded on/in Silica Gel - Katarzyna Trzeciak; Ewelina Wielgus; Sławomir Kaźmierski; Tomasz Pawlak; Marek J. Potrzebowski (MDPI AG, 2023)
The applicability of different solvent-free approaches leading to the amorphization of active pharmaceutical ingredients (APIs) was tested. Ethenzamide (ET), an analgesic and anti-inflammatory drug, and two ethenzamide cocrystals with glutaric acid (GLU) and ethyl malonic acid (EMA) as coformers were used as pharmaceutical models. Calcinated and thermally untreated silica gel was applied as an amorphous reagent. Three methods were used to prepare the samples: manual physical mixing, melting, and grinding in a ball mill. The ET:GLU and ET:EMA cocrystals forming low-melting eutectic phases were selected as the best candidates for testing amorphization by thermal treatment. The progress and degree of amorphousness were determined using instrumental techniques: solid-state NMR spectroscopy, powder X-ray diffraction, and differential scanning calorimetry. In each case, the API amorphization was complete and the process was irreversible. A comparative analysis of the dissolution profiles showed that the dissolution kinetics for each sample are significantly different. The nature and mechanism of this distinction are discussed.